Pengaruh Model pembelajaran Cooperative Integrated Reading and Composition Terhadap Kemampuan Membaca Pemahaman Cerita Pendek Peserta Didik Kelas V Sekolah Dasar - Adelia Putri Devita; Fadhil Purnama Adi (Universitas Sebelas Maret, 2025)
This study aims to determine whether there is an effect of the Cooperative Integrated Reading and Composition learning model on the ability to read comprehension of short stories of grade V elementary school students. This research is a quantitative research with quasi experimental design method with nonequivalent control group design. The sampling technique was carried out with one of the probability sampling techniques. The research sample consisted of two classes randomly selected from the population of grade V elementary school students in the orchid cluster. The experimental class used the CIRC learning model, while the control class used conventional learning. Data collection was carried out using test techniques. The data were analyzed using the independent sample t-test. Group discussion activities in this learning model also play a role in helping students understand the meaning of words the context of the story more deeply. The results of the analysis show a significance value (Sig. 2 tailed) of 0.007 <0.05, which means there is a significant difference between the learning outcomes of students in experimental and control classes. Thus, the Cooperative Integrated Reading and Composition learning model has a positive effect on the ability to read comprehension of short stories.